Synthesis and Characterization of Adsorbent Materials Magnetite Mercaptosilicate Ion Imprinted Polymer as Cadmium Ion Adsorbent - Nabela Viviana; Ngatijo; Restina Bemis; Diah Riski Gusti (Jurnal Riset Kimia, 2023)
Cadmium (Cd) is a toxic heavy metal with the active property of reacting with other components so that cadmium residues can quickly enter the food chain and cause cardiovascular, kidney, and cancer diseases. The purpose was to synthesize the magnetite mercaptosilicate ion imprinted polymer adsorbent material by forming Ion-Imprinted Polymer as a template, to analyze the characterization results using XRD and SEM-EDS, and to determine the adsorption test results for Cd metal ions. The results of the characterization of XRD show that there is a broad peak at a diffraction angle of 2θ= 20-220 with an amorphous structure, which is silica, and there is a high peak at a diffraction angle of 2θ= 35.55140 which indicates magnetite. The results of SEM analysis with magnifications of 500x, 1000x, and 5000x showed that the surface morphology of the particles was not uniform. For the EDS results, it can be seen that the components of the magnetite mercaptosilicate ion imprinted polymer material are elements C, O, Si, S, and Fe, with a mass percentage of 25.0%; 41.2%; 29.9%; 3.28% and 0.8%. The results of the adsorption test for the Magnetite-IIP-Mercaptosilika Material were able to adsorb Cd ions with the highest adsorption capacity of 10.536 mg/g at a concentration of 100 mg/L. Then the selectivity coefficient value of the Ion Cd metal ion is 2.32 greater than 1, indicating that the selectivity of the magnetite mercaptosilicate ion imprinted polymer material is much higher for Ion Cd metal ions than for Cu and Cr ions with a selectivity coefficient of 0.1 and 0.26.